Endoscopic third ventriculostomy for adults with hydrocephalus: creating a prognostic model for success: protocol for a retrospective multicentre study (Nordic ETV). Issue 1 (31st January 2022) - Tefre, Sondre; Lilja-Cyron, Alexander; Arvidsson, Lisa; Bartek, Jiri; Corell, Alba; Forsse, Axel; Glud, Andreas Nørgaard; Hamdeh, Sami Abu; Hansen, Frederik Lundgaard; Huotarinen, Antti; Johansson, Conny; Kämäräinen, Olli-Pekka; et al.
Abstract : Introduction: Endoscopic third ventriculostomy (ETV) is becoming an increasingly widespread treatment for hydrocephalus, but research is primarily based on paediatric populations. In 2009, Kulkarni et al created the ETV Success score to predict the outcome of ETV in children. The purpose of this study is to create a prognostic model to predict the success of ETV for adult patients with hydrocephalus. The ability to predict who will benefit from an ETV will allow better primary patient selection both for ETV and shunting. This would reduce additional second procedures due to primary treatment failure. A success score specific for adults could also be used as a communication tool to provide better information and guidance to patients. Methods and analysis: The study will adhere to the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis reporting guidelines and conducted as a retrospective chart review of all patients≥18 years of age treated with ETV at the participating centres between 1 January 2010 and 31 December 2018. Data collection is conducted locally in a standardised database. Univariate analysis will be used to identify several strong predictors to be included in a multivariate logistic regression model. The model will be validated using K-fold cross validation. Discrimination will be assessed using area under the receiver operating characteristic curve (AUROC) and calibration with calibration belt plots. Ethics and dissemination: The study is approved by appropriate ethics or patient safety boards in all participating countries. Trial registration number: NCT04773938; Pre-results .